Implications for the Cancellation Clause of General Insurance Policies Following the Constitutional Court Decision (No. 83/PUU-XXII/2024) - Ahmad Rendy; Elvan Fitransyah (SEAN Institute, 2026)
The legal status of general insurance policy cancellation clauses and their implications after the Constitutional Court Decision Number 83/PUU-XXII/2024. The research problem formulations are: (a) what is the legal status of general insurance policy cancellation clauses before and after the Constitutional Court decision, and (b) what are the legal implications of the decision on the wording and application of policy cancellation clauses. This research uses a juridical normative method, with a statutory and conceptual approach, and analyzes primary sources in the form of laws, related regulations, and Constitutional Court decisions, as well as secondary sources from journals and recent legal publications. The results of the study indicate that before the Constitutional Court decision, policy cancellation clauses gave the insurer the unilateral right to cancel the policy if the insured provided false information or concealed material facts, so that the insured was in a weak legal position. After the Constitutional Court Decision Number 83/PUU-XXII/2024, policy cancellation can only be done based on a written agreement between both parties or through a court decision, so that the position of the insured and the insurer becomes more balanced and constitutional. This study concludes that the Constitutional Court's decision provides clearer legal certainty and strengthens the protection of the insured